The Specifics of Training Highly Qualified Personnel in Postgraduate Studies Using Information and Communication Technologies in Russia and Abroad - Tatyana V. Sklyarova; Vladimir S. Malyshev (Peoples' Friendship University of Russia (RUDN University), 2021)
Modern requirements for Russian higher education in general and the system of training highly qualified personnel in particular arise from the necessity to improve the quality and efficiency in order to ensure the countrys international competitiveness in important areas of life. The research is aimed at filling the need for a detailed analysis of algorithms, frameworks and principles of organizing the process of training highly qualified personnel in graduate school, using information and communication technologies (ICT). The comparative nature of the work, which analyzes Russian and international experiences in this field, allows to obtain data that have not previously been systematized in the present context. The study is based on scientific and pedagogical publications of Russian and international authors. The purpose of the study is to consider the theoretical, methodological and organizational aspects of training graduate students, using ICTs in the selection of the analyzed material. The comparative analysis makes it possible to identify and systematize the specifics of informatization in training scientific and pedagogical personnel, the current implicit state of which complicates its interpretation in terms of the educational process organization and management. As a result, we can identify the following eight characteristics of the system of training highly qualified personnel in postgraduate studies using ICTs: theoretical and methodological foundations, characteristics of electronic learning systems, conditions for effective application and input data for their design, requirements for scientific supervisors and students, factors that update this type of training and a list of basic terms and concepts. The described characteristics can be used as a theoretical basis for further research, for example, in order to determine the actual parameters of designing the environment for students in graduate school as a means of scientific and pedagogical training of highly qualified personnel. The given descriptions of technologies in the context of the peculiarities of the impact of informatization on the implementation of the educational process, together with references to sources, allow to use the materials of the article as data for its planning and organization. The results of the research can be useful for specialists in designing, organizing, implementing and supporting the educational process in higher education using ICT tools: research supervisors, graduate students, managers and designers of educational programs.